Green Accounting At Hospital - Niar Astaginy; Fitriani Fitriani; Rahmawaty Arifiani; Shella Gilby Sapulette; Sri Gustini (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The purpose of this research is to investigate the use of Green Accounting in medical waste management at AMC Hospital. Bandung AMC Hospital is the subject of the study. The research methodology is qualitative. According to the study's findings, the hospital's spending for medical management waste. These expenses are reported in identical accounts, and the disclosure of incurred environmental costs has yet to be published in a distinct report from the parent report. Based on the notion of green accounting, this study reveals environmental cost reports and how to quantify the costs of environmental information supplied by hospitals for medical management.